Spatial magnetic imaging of non-axially symmetric vortex domains in cylindrical nanowire by transmission X-ray microscopy. Issue 37 (9th September 2022) - Fernandez-Roldan, Jose A.; Bran, Cristina; Asenjo, Agustina; Vázquez, Manuel; Sorrentino, Andrea; Ferrer, Salvador; Chubykalo-Fesenko, Oksana; del Real, Rafael P.
Abstract : By means of TXM, XMCD and modelling we determined the chirality and polarity of non-axially symmetric vortex structures in a CoNi/Ni multisegmented cylindrical nanowire, and a new 3D domain wall that is formed between vortices with opposite chirality. Abstract : The spatial magnetization texture of a cylindrical nanowire has been determined by Transmission X-ray Microscopy (TXM) and X-ray magnetic circular dichroism (XMCD). For this purpose, nanowires with designed geometry, consisting of CoNi/Ni periodic segments, have been grown by designed electrodeposition into alumina templates. Experimental data allow one to conclude the presence of mono- and trivortex magnetic domains in CoNi segments but, unusually, these states are characterized by an asymmetric XMCD contrast across the nanowire's section. Micromagnetic modelling shows non-trivial three-dimensional structures with ellipsoidal vortex cores and non-axially symmetric magnetization along the nanowire direction. The modelled TXM contrast of micromagnetic structures allows to correlate the experimental asymmetric XMCD contrast to the easy axis direction of the uniaxial magnetocrystalline anisotropy.